Psychological Terms In Marketing - Sevara Khamzaevna Khudoyberdieva (International Scientific and Current Research Conferences, 2020)
Places of application of psychological terms in Uzbek marketing terminology. This psychology is the most important area in marketing. The bulk of marketing terms are psychological terms